Fabrication And Characterisation Of Copper Composites Reinforced With Transition Metal Carbides Via Mechanical Alloying - Subhi, Nur Hawadah Mohd (2011)
In this study, high-energy ball milling also called mechanical alloying (MA) was applied to synthesis in situ copper based composite. Cu, M (M=W or Ti) and graphite powder mixture were mechanically alloyed for various milling time in a planetary ball mill. The nominal composition was Cu-28.72wt%W-1.87wt%C and Cu-9.67wt%Ti-2.42wt%C which corresponds to Cu-20vol%WC and Cu-20vol%TiC, respectively. With similar composition and milling time, the ex situ WC and TiC reinforced copper composite was also mixed by ball milling. Then the as-milled powder for both in situ and ex situ composites were compacted at 200 to 400 MPa and sintered in vacuum furnace at 900ºC.